Answer: The correct option is
(C)
![y=-6\left(x-(1)/(4)\right)^2+(19)/(8).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3rgzl2gn0bne1wtjw0yx8okj8zq1cyrj8c.png)
Step-by-step explanation: We are given to select the equation that is the vertex form of he following equation :
![y=-6x^2+3x+2~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6bwl0w636wrtxxoc4qrdsvgu2kw0c8asg4.png)
We know that
the vertex form of a function y = f(x) is written as
where (h, k) is the vertex.
From equation (i), we have
![y=-6x^2+3x+2\\\\\\\Rightarrow y=-6\left(x^2-(1)/(2)x\right)+2\\\\\\\Rightarrow y=-6\left(x^2-2* x*(1)/(4)+\left((1)/(4)\right)^2\right)+2+6* \left((1)/(4)\right)^2\\\\\\\Rightarrow y=-6\left(x-(1)/(4)\right)^2+2+(6)/(16)\\\\\\\Rightarrow y=-6\left(x-(1)/(4)\right)^2+2+(3)/(8)\\\\\\\Rightarrow y=-6\left(x-(1)/(4)\right)^2+(16+3)/(8)\\\\\\\Rightarrow y=-6\left(x-(1)/(4)\right)^2+(19)/(8).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ceugiol5c0pe3v2s3d11j16vtpwnntpmaq.png)
Thus, the required vertex form of the given equation is
![y=-6\left(x-(1)/(4)\right)^2+(19)/(8).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3rgzl2gn0bne1wtjw0yx8okj8zq1cyrj8c.png)
Option (C) is CORRECT.